A novel mutation of AMHR2 in two brothers with persistent Müllerian duct syndrome and their intracytoplasmic sperm injection outcome. Issue 10 (4th September 2021) - Fang, Jianzheng; Gao, Gao; Liu, Jinyong; Cai, Lingbo; Cui, Yugui; Yang, Xiaoyu
Abstract: Background: Persistent Müllerian duct syndrome (PMDS) is defined as the presence of Müllerian duct derivatives in an otherwise normally virilized 46, XY male. It is usually caused by homozygous or compound heterozygous mutations in either the anti‐Müllerian hormone ( AMH ) or AMH receptor type 2 ( AMHR2 ) genes. The main purpose of the study is to determine the novel mutations of AMHR2 in PMDS patients and their intracytoplasmic sperm injection outcomes (ICSI). Methods: Whole‐exome sequencing (WES) was carried out. Sanger sequencing was used to detect mutations in AMHR2. The pathogenicity of the identified variant and its possible effects on the protein were evaluated with in silico tools. The expression level of AMHR2 was determined by Western blotting. The spermatogenic function was evaluated by testicular sperm aspiration and histopathologic examination. The ICSI outcomes were recorded. Results: We present two brothers with a history of bilateral cryptorchidism with orchidopexy and infertility due to azoospermia. A novel compound heterozygous mutation of c.1219C>T [p.R407X] and c.1387C>T [p.R463C] in exons 9 and 10 of AMHR2 (NM_020547.2) was detected by whole‐exome sequencing (WES). Spermatozoon could be retrieved from the two patients by testicular aspiration following intracytoplasmic sperm injection (ICSI) due to azoospermia. Finally, patient 1 had two healthy boys and patient 2 failed to conceive after three ICSI attempts. Conclusion: The spermatozoa could obtain from PMDS patients due to azoospermia. For patients with bilateral cryptorchidism, PMDS should be included in the differential diagnosis and that genetic counseling needs to be considered when they seek reproductive help. Abstract : The spermatozoa could obtain from PMDS patients due to azoospermia. For patients with bilateral cryptorchidism, PMDS should be included in the differential diagnosis and that genetic counseling needs to be considered when they seek reproductive help.